The Implementation of Archive Learning Based on the Kurikulum 2013 - Septianingrum, Ayunda Dwi; Indartono, Setyabudi (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to determine the extent to which the application of archive learning based on the Kurikulum 2013 conducted by XII students in Office Administration at the SMK Negeri 1 Tepus. This is a evaluative study in which the methods used are Context, Input, Process and Product (CIPP). Data collection is obtained through interviews, observation, and documentation. The data analysis using interactive analysis by Miles and Huberman consists of data collection, data reduction (data reduction), data presentation (data display) and conclusions (conclusions / verification). The results of the study indicate that the implementation of archive learning is considered, starting with preparing syllabus and lesson plans (RPP) so that they can be implemented in the classroom starting from Opening Activities, Core Activities, and Closing Activities. However, in real practice, these activities are considered to be less in line with the implementation of the Kurikulum 2013 because there have been many obstacles felt by teachers, students, and school infrastructure.